A wideband frequency synthesizer for a receiver application at multiple frequencies - 王小松 黄水龙 陈普锋 雷牡敏 李志强 张海英 (Journal of semiconductors, 2010)
An integer-N frequency synthesizer for a receiver application at multiple frequencies was implemented in 0.18μm 1P6M CMOS technology. The synthesizer generates 2.57 GHz, 2.52 GHz, 2.4 GHz and 2.25 GHz local signals for the receiver. A wide-range voltage-controlled oscillator （VCO） based on a reconfigurable LC tank with a binaryweighted switched capacitor array and a switched inductor array is employed to cover the desired frequencies with a sufficient margin. The measured tuning range of the VCO is from 1.76 to 2.59 GHz. From the carriers of 2.57 GHz, 2.52 GHz, 2.4 GHz and 2.25 GHz, the measured phase noises are -122.13 dBc/Hz, -122.19 dBc/Hz, -121.8 dBc/Hz and -121.05 dBc/Hz, at 1 MHz offset, respectively. Their in-band phase noises are -80.09 dBc/Hz, -80.29 dBc/Hz, -83.05 dBc/Hz and -86.38 dBc/Hz, respectively. The frequency synthesizer including buffers consumes a total power of 70 mW from a 2 V power supply. The chip size is 1.5 × 1 mm2.